Does financial inclusion reduce income inequality in South Sumatra, Indonesia? - Sri Andaiyani; Nazeli Adnan; Yunisvita Yunisvita; Muhammad Riswan (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2022)
Purpose — To analyze the impact of financial inclusion toward income distribution inequality in South Sumatra, Indonesia.Research method — The analysis method in this paper is panel regression model. This methodology is used to avoid bias specifications in the model. This paper applied three dimensions of financial which are financial penetration, access to financial services and use of financial services. The data was taken from the Financial Services Authority, Central Bank of Indonesia and the Central Statistics Agency. The data was time series from 2010-2017 and cross section from 9 rural and urban in South Sumatra, Indonesia.Result — The result showed that each district in South Sumatera has divergent degree of financial inclusion index. The degree of financial inclusion index in city area has a relatively higher financial index than hinterland areas. Based on the result of estimations, the impact of financial inclusion index on income inequality is positive and significant. This evidence proved that financial inclusion does not reduce income inequality in South Sumatra, Indonesia.Recommendation — Financial institutions are more motivated to lend to groups like farmers, the impoverished, and small and micro businesses. It is vital for the government to provide more fair financial services amongst regencies and cities.